Strategi Pembelajaran dengan Model Pendekatan Pada Peserta Didik Sekolah Menengah Pertama Agar Tercapainya Tujuan Pendidikan - Hidayati Hidayati; Syarah Syarif; Gusmaneli Gusmaneli (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
Learning for junior high school students must have the right strategy, in a learning process we need to have an approach to students so that we can know each child's character, so that it is easy for us to determine what learning model is suitable for the students who will be educated. . This method is to make it easier for teaching staff and not to simply give learning models without any approach and this will have consequences for junior high school students if we give the wrong strategy. In the world of education, several terms such as strategy, approach, model and method are often used to describe teaching and learning situations. And these terms are often inconsistent and often overlap in their use. To distinguish and clarify the differences between each of these terms, they need to be studied and discussed contextually and comprehensively. This needs to be done, in order to avoid further confusion and misunderstanding of the meaning of some of these terms. This article will specifically try to explain these four terms, because these four terms are most widely used and referred to by practitioners in the field of education. Clarification of the terms will help to untangle the confused understanding of meaning in the world of education and the world of literacy.